Pelatihan Pembuatan Produk Kacang Cokelat untuk Meningkatkan Penghasilan Masyarakat Desa Bandasoleh, Kecamatan Kokop, Kabupaten Bangkalan, Madura - Fauzan, Fauzan; Luluk Sudarsini, Anila (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
One of the ways to increase the value of the natural resources produced by the Bandasoleh community, especially peanuts, is by processing peanuts into chocolate nuts, which adds to the community's creative ideas for processing peanuts into a snack product that can be sold in markets and shops in general. In this case, students offer attractive packaging to increase consumer purchasing power. Then in terms of packaging, the people of Bandasoleh pay less attention, so we are here to offer to the public that if the product is to be appropriate and seen as attractive, it must have attractive packaging, in addition to considering the needs of making the product so that it can determine the price according to the expenditure and the unit price of the product. This training will add to the community's experience and insight in developing natural resources around them into business ideas.